2000
DOI: 10.1089/ars.2000.2.2-213
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Redox System in the Control of Stress-Induced Apoptosis

Abstract: The plasma membrane of animal cells contains an electron transport system based on coenzyme Q (CoQ) reductases. Cytochrome b5 reductase is NADH-specific and reduces CoQ through a one-electron reaction mechanism. DT-diaphorase also reduces CoQ, although through a two-electron reaction mechanism using both NADH and NADPH, which may be particularly important under oxidative stress conditions. Because reduced CoQ protects membranes against peroxidations, and also maintains the reduced forms of exogenous antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 134 publications
1
62
0
Order By: Relevance
“…There are two other enzymes important for the intracellular metabolism of ascorbate, namely thioredoxin reductase and cytochrome-b5-reductase (48,49). There are several isoforms of thioredoxin reductase and cytochrome-b5-reductase in mice, but there is no commercial antibody to detect all of the different isoforms of these enzymes.…”
Section: Vitamin C Normalizes Gsh Metabolism In the Liver Of Wrn δHelmentioning
confidence: 99%
“…There are two other enzymes important for the intracellular metabolism of ascorbate, namely thioredoxin reductase and cytochrome-b5-reductase (48,49). There are several isoforms of thioredoxin reductase and cytochrome-b5-reductase in mice, but there is no commercial antibody to detect all of the different isoforms of these enzymes.…”
Section: Vitamin C Normalizes Gsh Metabolism In the Liver Of Wrn δHelmentioning
confidence: 99%
“…NQO1 is a NAD(P)H-dependent reductase that is translocated to the inner surface of the PM under stress conditions (30). Dietary CoQ is important in maintaining levels of reduced CoQ and ␣-tocopherol in the PM, thereby protecting the PM from lipid peroxidation (31). In the present study the effects of aging and CR on the brain PMRS and PM-associated oxidative stress were investigated in rats.…”
mentioning
confidence: 97%
“…Inhibition of the PMOR in q°cells (Larm et al 1994), and other cell lines , causes cell death, highlighting its vital role in redox homeostasis. The PMOR also modulates cellular processes that are redox sensitive, including cell growth, intracellular signaling and apoptosis (reviewed in Baker and Lawen 2000), and it maintains plasma membrane antioxidant systems, preventing oxidative stress-induced cell death (reviewed in Villalba and Navas 2000). Although the PMOR has been extensively studied in non-neuronal cells, to our knowledge, studies of the PMOR in primary CNS neurons have not been reported.…”
mentioning
confidence: 99%